Propriedades reológicas e efeito da adição de sal na viscosidade de exopolissacarídeos produzidos por bactérias do gênero Rhizobium - Aranda-Selverio, Gabriel [UNESP]; Penna, Ana Lúcia Barretto [UNESP]; Campos-Sás, Luciana Frizarin [UNESP]; Santos Junior, Osvaldo dos [UNESP]; Vasconcelos, Ana Flora Dalberto [UNESP]; Silva, Maria de Lourdes Corradi da [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP]; Campanharo, João Carlos [UNESP]; Silveira, Joana Léa Meira (Sociedade Brasileira de Química, 2010)
Viscosity of some polysaccharide solutions supports that these molecules can be applied in food sectors. Four exopolysaccharides (R1, R2, R3, R4) produced by different Rhizobium strains were selected. Sugar composition and differences in the uronic acid contents suggests that chemical structure of these molecules can vary when different culture conditions and strains are analyzed. The Power Law was the rheological model used to represent the experimental data of shear stress versus shear rate. All exopolysaccharides showed non-Newtonian behavior, with pseudoplastic characteristics. R1, R2 and R4 showed a slight increase in viscosity in the presence of 0,2 M NaCl.
Rheological properties and effect of the salt addition on the exopolysaccharides viscosity produced by bacteria of Rhizobium genus
Keywords: rheological behaviour; exopolysaccharides from Rhizobium; Pseudoplastic solution